Multiliteracies-translanguaging conceptual model framework for student agency in English as foreign language contexts - Zhou, Jie; Lee, Sze Seau; Kew, Si Na; Liew, Chee Yoong (International Journal of Evaluation and Research in Education (IJERE), 2024)
Developing student agency in formal education leads to favorable impacts on cognitive development as well as learning experiences that culminate in a strong foundation for lifelong learning, which is crucial for employability. However, theoretical grounded pedagogical approaches for student agency are still at the nascent level of conception. Assuming that student agency can be developed in the English classroom, this article aims to propose a conceptual model framework based on multiliteracies and translanguaging to address the pedagogical gaps in student agency with examples from the English as foreign language educational contexts. The first objective is to identify pedagogical guidelines for student agency from multiliteracies and the second objective is to identify pedagogical guidelines for student agency from translanguaging. Jaakola’s model approach guided the analytical review of literature to address the knowledge gap in pedagogy. Findings underline the affordances of multiliteracies for scaffolding multimodal meaning-making and the affordances of translanguaging for motivating active participation and expanding linguistic repertoire of students. These affordances can guide the developments of context-bound resources and relational resources of student agency. The proposed framework can be a reference point for curriculum designers or teachers to develop approaches for student agency.